Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)
Organisé par l’Observatoire interdisciplinaire de création et de recherche en musique et le Centre des musiciens du monde, le colloque Femmes musiciennes du monde visait à explorer les parcours professionnels de musiciennes migrantes. Des conférences et tables rondes ont fait intervenir des chercheuses en sociologie, anthropologie, musicologie et ethnomusicologie ainsi que des musiciennes ayant immigré à Montréal. De la combinaison de ces savoirs scientifique et expérientiel s’est dégagée une série de difficultés et défis récurrents pour les femmes en musique : invisibilisation du travail, différenciations et discriminations genrées dans un milieu majoritairement masculin, enjeux liés au corps féminin ainsi qu’à la mobilité géographique. Or, il s’est aussi affirmé des spécificités d’expériences, de profils et de stratégies selon les parcours migratoires. Cette note de terrain synthétise les principaux constats, mais aussi les limites des discussions de ce colloque avant d’identifier quelques-uns des nombreux efforts qu’il reste à déployer pour mieux comprendre les réalités de telles artistes.
Keywords: 2000 à aujourd'hui; 2020-2029; DIG; agentivité; anthropologie; approches et analyses; arts; corps; discipline; discriminations; femmes* artistes; femmes* immigrantes; femmes* musiciennes; intersectionnalité; invisibilité historique; musique; périodes historiques; racisme; ressource en ligne; savoir expérientiel; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; violences

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail